Tracce di iper-in-visibilità Rappresentazione e disparità di genere: uno sguardo sulla quotidianità - Bucchetti, Valeria; Casnati, Francesca (Design della comunicazione, 2022)
Each contribution provides evidences to document some areas of the media landscape that are still critical, as they are characterized by design logics that underlie male supremacy. These areas were deeply observed by the authors to reveal the mechanisms that influence the stereotyping of female identity. The studies collected in the book pertain to different thematic areas, observed through a dual lens, that of communication design and gender studies. The reflection about the representational patterns and the power of the iconic act constitutes the underlying axis of the text. Through focused observations - stock visual content, mainstream music videos, visual ageism, pictographic languages, menstruonormativity, to mention a sampling of a few - the book gives evidence to the implications and repercussions bearing on the close concatenation that is established between visibility, representativeness, and social recognition.